General Aspects of the Inflammatory Reaction in COVID-19 (International Seven Journal of Multidisciplinary, 2023)
Today, we are faced with one of the most contagious viral infections in history, the pandemic produced by the SARS-CoV-2 coronavirus, the etiologic agent of the WHO-appointed Organization as COVID-19. Coming to the attention of many in late 2019, COVID-19, which already existed prior to that date, gained great prominence after promoting a pandemic that lasted through the years 2020 and 2021 and claimed thousands of victims worldwide. Because its pathogenesis and mechanism of attack were practically unknown and little studied at the time, health organizations could do little in a short period of time, and many people from all parts of the world suffered the consequences of the disease, directly or indirectly. The side effects for each citizen were often different, ranging from the symptoms of a common cold to a severe acute respiratory syndrome, and becoming more lethal in patients with diabetes, hypertension, kidney failure, obesity, and cardiovascular disease, among others. From then on, the existence of numerous clinical forms in COVID-19 was realized and the need for studies to elucidate how each one works by understanding the specific role of TCD4+ and TCD8+ lymphocytes in directing inflammation, as well as understanding how the reaction happens and what "motivates" the lymphocytes to promote it (SURYASA et al., 2021; SETTE, CROTTY, 2021; GALVÃO, DELLALIBERA-JOVILIANO 2022).